Do Employment Protection Reforms Affect Well-Being? - Vanessa Dräger (Institute for the Study of Labor (IZA), 2015)
This paper examines reforms in German employment protection for permanent workers (EPLP) on workers' well-being proxied by life satisfaction. Using variation in how the reforms affected firms of different sizes, I apply a difference-in-differences approach in conjunction with individual fixed effects. I find that life satisfaction of temporary workers decreases by around 0.5 (11-point scale) when EPLP decreases. I investigate effect heterogeneity and discuss mechanisms. Placebo tests are conducted. An increase in EPLP had no effect. Due to the design of the EPLP reforms, the majority of permanent workers did not face major changes in EPLP.
Keywords: J32; J38; 330; life satisfaction; well-being; employment protection reforms; quasi-experiment; difference-in-difference